JOHNSENITE-(CE): A NEW MEMBER OF THE EUDIALYTE GROUP FROM MONT SAINT-HILAIRE, QUEBEC, CANADA - Grice J.D.; Gault R.A. (My University, 2006)
Johnsenite-(Ce), ideally Na12(Ce,La,Sr,Ca,□)3 Ca6Mn3Zr3W(Si25 O73)(CO3)(OH,Cl)2, is a new member of the eudialyte group from Mont Saint-Hilaire, Quebec, and is the W analogue of zirsilite-(Ce). It occurs as deeply etched, skeletal crystals to 4 mm and aggregates of crystals to 1 cm. Associated minerals include, albite, calcite, pectolite aegirine, fluorapophyllite, zirsilite-(Ce), a burbankite- group phase, dawsonite, rhodochrosite, epididymite, galena, molybdenite, pyrite, pyrrhotite, quartz, an amphibole-group mineral, sphalerite, stillwellite-(Ce), titanite, cerite-(Ce), tuperssuatsiaite, steacyite, catapleiite, zakharovite, natrolite and microcline. It is transparent to translucent with a vitreous luster and white streak. It is brittle with a Mohs hardness of 5-6. It has no discernable cleavage or parting and an uneven fracture. It is uniaxial negative with ω 1.648(1) and ε 1.637(1). It is trigonal, space group R3m, a 14.237(3) and c 30.03(1) Å, V 5271(2) Å3, Z = 3. The eight strongest X-ray powder-diffraction lines, measured for johnsenite-(Ce) [d in Å (I)(hkl)] are: 11.308(95)(101), 9.460(81)(012), 4.295(34)(205), 3.547(36)(220), 3.395(38)(131), 3.167(75)(217), 2.968(100)(315) and 2.849(81)(404). The infrared spectrum of johnsenite-(Ce) is given. An average result of eight electron-microprobe analyses, including three on the grain used for the structure determination, gave Na2O 10.47, K2O 0.25, CaO 8.98, SrO 1.60 MnO 5.43, FeO 1.61, Y2O3 0.70, La2O3 1.56, Ce2O3 3.01, Pr2O3 1.14, Nd2O3 0.89, Sm2O3 0.12, Gd2O3 0.33, Dy2O3 0.14, TiO2 0.73, ZrO2 9.60, HfO2 0.04, Nb2O5 0.82, WO3 5.23, SiO2 43.16, Cl 0.77, CO2 (1.27), H2O (0.32), O = Cl-0.17, total 97.99 wt. %. Concentrations of CO2 and H2O were calculated by stoichiometry based on results from the crystal-structure analysis. The empirical formula of johnsenite-(Ce), based on 29 (Si4+, Zr4+, Ti4+, Hf4+, Nb5+, W6+) cations and 1 (CO3) as determined in the crystal-structure analysis, is: Na11.74([Ce0.64 La0.33Dy0.03]∑1.00Sr0.54 Ca0.51Y0.22K0.19)∑2.46 (Ca5.06[Pr0.24Nd0.18Gd0.06 Sm0.02]∑0.50Mn0.44)∑6 (Mn2.22Fe0.78)∑3(Zr2.71 Ti0.32Hf0.01)∑3.04(W0.78 Nb0.21)∑0.99Si24.97O73 (CO3)(OH,Cl0.75)∑2. Dmeas. = 3.24(3) g/cm3; Dcalc. = 3.23 g/cm3. The structure consists of four layers. The layering is distinctly polar, as indicated by the X-ray-diffraction intensity statistics, layer composition and electrostatic potential of individual crystals. The new species is named after Ole Johnsen, of the Geological Museum, University of Copenhagen, Denmark.
Keywords: CRYSTAL STRUCTURE; EUDIALYTE; JOHNSENITE-(CE); MONT SAINT-HILAIRE; NEW MINERAL SPECIES; QUEBEC